PENGEMBANGAN BAHAN AJAR IPA BERBASIS MULTIMEDIA INTERAKTIF KELAS V SDN 1 PETELUAN INDAH - HARTINI, HIDAYAH LENSIMIA; ISTININGSIH, SITI; NISA, KHAIRUN (LEARNING : Jurnal Inovasi Penelitian Pendidikan dan Pembelajaran, 2024)
This development research aims to produce products in the form of interactive multimedia-based science teaching materials for grade V SDN 1 Peteluan Indah that are feasible and practical to implement. This research is a type of Research and Development (R&D) research using the 4D development model which consists of the defining stage (define), the planning stage (design), the development stage (develop), and the dissemination stage (disseminate). The subjects of this study were 22 fifth grade students of SDN 1 Peteluan Indah. Meanwhile, the object of this research is teaching materials for grade V SDN 1 Peteluan Indah in the form of interactive multimedia. Validation was carried out to determine the feasibility of interactive multimedia-based science teaching materials developed. Validation was obtained using a data collection method in the form of a questionnaire given to material experts, media experts and learning experts. The response of students and educators (teachers) was obtained using a questionnaire data collection method. The results of material expert validation were obtained at 85.56% with a valid category, media experts obtained 88.24% with a valid category and learning experts obtained 92.50% with a very valid category.  While the results of the educator's response were obtained at 93.75% with a very practical category, the results of the small group trial obtained an average percentage of 91.85% with very practical criteria and the large group trial obtained an average percentage of 89.60% with practical criteria. So that interactive multimedia-based science teaching materials are feasible from valid and practical aspects to be used in the learning process in class V SDN 1 Peteluan Indah on theme 6 sub-theme 2 heat transfer around us. ABSTRAKPenelitian pengembangan ini bertujuan untuk menghasilkan produk berupa bahan ajar IPA berbasis multimedia interaktif kelas V SDN 1 Peteluan Indah yang layak dan praktis untuk diterapkan. Penelitian ini merupakan jenis penelitian Research and Development (R&D) dengan menggunakan model pengembangan 4D yang terdiri dari tahap pendefinisian (define), tahap perencanaan (design), tahap pengembangan (develop), dan tahap penyebaran (disseminate). Subjek penelitian ini adalah peserta didik kelas V SDN 1 peteluan indah sebanyak 22 orang. Sedangkan untuk objek penelitian ini adalah bahan ajar kelas V SDN 1 Peteluan Indah yang berupa multimedia interaktif. Validasi dilakukan untuk mengetahui kelayakan terhadap bahan ajar IPA berbasis multimedia interaktif yang dikembangkan. Validasi diperoleh dengan menggunakan metode pengumpulan data berupa angket yang diberikan kepada ahli materi, ahli media dan ahli pembelajaran. Respon peserta didik dan pendidik (guru) diperoleh dengan metode pengumpulan data berupa angket. Hasil validasi ahli materi diperoleh sebesar 85,56% dengan kategori valid, ahli media diperoleh sebesar 88,24% dengan kategori valid dan ahli pembelajaran diperoleh sebesar 92,50% dengan kategori sangat valid.  Sedangkan hasil respon pendidik diperoleh sebesar 93,75% dengan kategori sangat praktis, hasil uji coba kelompok kecil diperoleh rata-rata persentase sebesar 91,85% dengan kriteria sangat praktis dan uji coba kelompok besar diperoleh rata-rata persentase sebesar 89,60% dengan kriteria praktis. Sehingga bahan ajar IPA berbasis multimedia interaktif sudah layak dari aspek valid dan praktis untuk digunakan dalam proses pembelajaran di kelas V SDN 1 Peteluan Indah pada tema 6 sub tema 2 perpindahan kalor di sekitar kita.